Auto building model in Simulink environment for microgrid application - Lu, Methavee Yi Hui (Nanyang Technological University, 2020)
A micro-grid is a group of sources forming a small-scale power grid that can operate independently or in connection with the utility grid. With the depletion of conventional sources along with an increase of environmental concerns, renewable energy systems are gaining importance. Also, with the increased interests in decentralized power systems, micro-grids are becoming increasingly relevant. A micro-grid power system includes diesel generators, renewable sources like photovoltaic and wind turbine generators, energy storages, and loads connected in AC or DC bus with a power management system. This project aims to design a user-friendly Auto building model, that allow users to evaluate various preliminary micro-grid system configurations in terms of design, reliability and efficiency, before actual implementation. The proposed solution aims to prevent a poorly designed micro-grid, which could incur financial losses due to future corrective restructuring of systems.